"I learn for a job promotion!": the role of outcome-focused career goals in motivating distance learners to learn. Issue 3 (3rd July 2018) - Ng, Clarence
ABSTRACT: Outcome-focused career goals are concerned about studying for tangible career benefits. To what extent do these goals motivate distance learners to learn? Using a mixed-method design, Study 1 found that career-focused learners, when compared with noncareer-focused counterparts, had a propensity to endorse outcome-focused career goals, use surface strategies, value their learning, and achieve better course results. Interview findings showed that career-focused learners used a strategic approach to ensure the timely completion of tasks and examination preparation. Study 2 located two groups of career-focused learners (autonomous and controlled) who endorsed outcome-focused career goals, alongside a noncareer-focused group. MANOVA analyses found that autonomous and noncareer-focused learners had engaged learning patterns. Although controlled learners were less engaged in learning, they achieved better results. It was concluded that outcome-focused career goals are significant sources of motivation for distance learners, despite being extrinsic to learning.